Protective Effects of Chrysin Against Drugs and Toxic Agents - Samarghandian, Saeed (Dose Response, 2017)
ISSUES: Polyphenolic compounds, especially flavonoids, are known as the most common chemical class of phytochemicals, which possess a multiple range of health-promoting effects. Flavonoids are ubiquitous in nature. They are also present in food, providing an essential link between diet and prevention of several diseases. APPROACH: Chrysin (CH), a natural flavonoid, was commonly found in propolis and honey and traditionally used in herbal medicine. A growing body of scientific evidence has shown that CH possesses protective effects against toxic agents in various animal tissues, including brain, heart, liver, kidney, and lung. KEY FINDINGS: This study found that CH may be effective in disease management induced by toxic agents. However, due to the lack of information on human, further studies are needed to determine the efficacy of CH as an antidote agent in human. CONCLUSION: The present article aimed to critically review the available literature data regarding the protective effects of CH against toxic agent–induced toxicities as well as its possible mechanisms.